Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1969
DOI: 10.1149/1.2411780
|View full text |Cite
|
Sign up to set email alerts
|

Growth Rate and Surface Morphology Studies in the GeCl[sub 4]-H[sub 2] System

Abstract: Growth rate studies of the GeC14-H2 reaction are reported for an epitaxial system. The experimentally observed deposition rates are described in terms of a "quasi-equilibrium" model in which only a limited portion of the gas achieves equilibrium composition. Smooth surfaces are obtained under conditions where epitaxial growth appears to be mass transport controlled. For any given Ge concentration, the observed dependence of growth rate on temperature and substrate orientation indicates that a surface limitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1972
1972
2000
2000

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…2 and 3 of Ref. (15). Thus, we conclude that a surface rate limitation probably has not been reached in the neighborhood of the ridge, although any increase in transport rates unavoidably shifts the system closer to that condition.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…2 and 3 of Ref. (15). Thus, we conclude that a surface rate limitation probably has not been reached in the neighborhood of the ridge, although any increase in transport rates unavoidably shifts the system closer to that condition.…”
Section: Discussionmentioning
confidence: 54%
“…Ge/H2 ----3.6 • 10-4; linear gas stream velocity, 175 cm/min; growth times were constant at 11 min. Under these conditions the growth rate was constant at 0.099 ~m/min (15), and ridge growth immediately adjacent to the oxide was noted for all samples. Ridge measurement.--Vertical profiles of the ridge were taken across the shorter dimension of the pads employing a stylus gauge.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The HCI formed may, in turn, react with the solid Ge to form other gaseous species detected in the GeC14-H 2 system [60], such as GeC12 and GeCI 3. The situation in the reactor is considerably more complex than that suggested by the overall reaction…”
Section: Epitaxy Using Germanium Tetrachloride Gec14mentioning
confidence: 99%
“…Other investigators [67][68][69][70][71][72] examined growth conditions and surface morphology for different crystallographic orientations. Silvestri [60] observed that at deposition temperatures from 600-850°C, the deposition rate (less than about 2x 10-3 Torr) epitaxial growth of Ge was observed on Ge (100) surfaces, whereas at higher partial pressures, etching of the Ge occurred. They…”
Section: Miller and Grieco [65] Studied The Etching Reactions Involvimentioning
confidence: 99%